Faktor Risiko Yang Berhubungan Dengan Kejadian Hipertensi Pada Wanita Dewasa Di Wilayah Kerja Puskesmas Sitinjak Kecamatan Angkola Barat Kabupaten Tapanuli Selatan - Dinda Putri Aditya; Thomson P Nadapdap; Mappeaty Nyorong (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension is a condition with blood pressure that exceeds normal limits. If hypertension is not controlled properly, it can cause damage to blood vessels and can even lead to the risk of death. According to the 2018 Riskesdas, it shows that the prevalence of people with high blood pressure is 34.11%. The prevalence of high blood pressure in women is 36.85% higher than that of men, 31.34%. Data obtained from the Sitinjak Health Center, Angkola Barat District, South Tapanuli Regency, the number of hypertension sufferers has increased from 2019-2021. This study aims to determine the risk factors (hereditary, obesity, smoking habits, eating habits, and physical activity) associated with the incidence in adult women in the Working Area of ??the Sitinjak Health Center, Angkola Barat District, South Tapanuli Regency. The type of research used was an analytical design. cross sectional. The population in this study was adult women aged 30-49 years in the Working Area of ??the Sitinjak Health Center, Angkola Barat District, South Tapanuli Regency, as many as 105 people. The sample in this study amounted to 51 people, the sampling technique was this study using a non-probability sampling technique, namely accidental sampling. Data were obtained from the Community Health Center and through interviews using a questionnaire. Methods of data analysis were analyzed univariately, bivariately using Chi-Square test at 95% confidence level (P<0.05) and multivariate test with multiple regression tests. The results showed that hereditary variables, obesity, eating habits were related to the incidence of hypertension. The most dominant variable is eating habits. It is suggested to respondents to change their bad living habits for the better to prevent hypertension and for health workers to conduct health education to the public about how to prevent hypertension, for example by reducing consumption of foods that trigger hypertension.